Prevalence of Hypothyroidism in Patients with Dyslipidemia: Tehran Thyroid Study (TTS) - Khazan, M.; Amouzegar, A.; Gharibzadeh, S.; Mehran, L.; Tohidi, M.; Azizi, F. (Hormone and Metabolic Research, 2014)
Hypothyroidism is a relatively common endocrine disorder usually accompanied with changes in serum lipid profiles. The purpose of this study was to assess the association between dyslipidemia and hypothyroidism in a population-based study. In this cross-sectional study, 2 315 dyslipidemic patients, aged 20–90 years (mean age: 38.1±13.2 years), were selected from among 5 760 participants of Tehran Thyroid Study and divided into 3 groups, the subclinical hypothyroid, overt hypothyroid, and euthyroid subjects, based on national reference ranges. Serum lipid profiles, free thyroxine (FT4), thyroid stimulating hormone (TSH), and thyroid peroxidase antibody (TPOAb) were measured in all subjects. In subjects with dyslipidemia and nondyslipidemia, the prevalence of subclinical was 7% and 4.1%, respectively, and for clinical hypothyroidism 3% and 1.2%, respectively. In dyslipidemic subjects, the mean low density lipoprotein-cholesterol (LDL-C) levels differed significantly (p=0.03) among the overt hypothyroid (144.3±36.1), subclinical hypothyroid (129.3±39.2), and euthyroid (132.7±39.0) groups. In the overt hypothyroid group, mean total cholesterol level was higher than in the normal group, but not significant. There were no differences in median triglycerides (TG) and mean high density lipoprotein-cholesterol (HDL-C) levels among the 3 groups mentioned. After adjusting for age and sex, hypothyroidism was not related to elevated serum lipid profiles in patient with dyslipidemia. In conclusion, there is significant difference in the prevalence of subclinical and clinical hypothyroidism between nondyslipidemic and dyslipidemic subjects; after adjustment for age and sex the presence of dyslipidemia did not predict the presence of hypothyroidism.
Keywords: dyslipidemia; overt hypothyroidism; subclinical hypothyroidism